GENDER IN ISLAMIC INHERITANCE - Rahmatullah Rahmatullah (IAIN Tulungagung, 2020)
This article examines a debate on gender equality, which is considered by some to be in conflict with the Qur’an, an-Nisa [4]:11. Using a philosophical approach and analyzing Sa‘ id Ramadan al-Buti’s concept of inheritance in his Al-Mar’ah Bayna Tughyan al-Nizam al-Gharbi wa Lata’if al-Tashri’ al-Rabbani, this paper tries to refute this allegation and offers a more gender-friendly interpretation. For al-Buti, the verse has actually liberated women because the provisions are caused by the responsibilities imposed by Islam on men as prospective husbands, not on women. On the contrary, if women are more empowered than men, that becomes a moral issue, not a shari’a one. Women have been given freedom by the shari’a in order to determine their choice to participate in bringing about stability in life. A condition that women are more empowered than men will not be the cause of changes in the shari’a’s provisions concerning inheritance.